Selection and validation of reference genes for RT-qPCR-based analyses of Anastatus japonicus Ashmead (Hymenoptera: Helicopteridae) - Liu, Zixin; Xiao, Junjiang; Xia, Yue; Wu, Qifeng; Zhao, Can; Li, Dunsong (Frontiers in Physiology, 2022)
RT-qPCR remains a vital approach for molecular biology studies aimed at quantifying gene expression in a range of physiological or pathological settings. However, the use of appropriate reference genes is essential to attain meaningful RT-qPCR results. Anastatus japonicus Ashmead (Hymenoptera: Helicopteridae) is an important egg parasitoid wasp and natural enemy of fruit bugs. While recent transcriptomic studies have analyzed gene expression profiles in A. japonicus specimens, offering a robust foundation for functional research focused on this parasitoid, no validated A. japonicus reference genes have yet been established, hampering further research efforts. Accordingly, this study sought to address this issue by screening for the most stable internal reference genes in A. japonicus samples to permit reliable RT-qPCR analyses. The utility of 8 candidate reference genes (ACTIN, TATA, GAPDH, TUB, RPL13, RPS6, EF1α, RPS3a) was assessed under four different conditions by comparing developmental stages (larvae, pupae, adults), tissues (abdomen, chest, head), sex (male or female adults), or diapause states (diapause induction for 25, 35, 45, or 55 days, or diapause termination). RefFinder was used to calculate gene stability based on the integration of four algorithms (BestKeeper, Normfinder, geNorm, and Ct method) to determine the optimal RT-qPCR reference gene. Based on this approach, RPS6 and RPL13 were found to be the most reliable reference genes when assessing different stages of development, while ACTIN and EF1α were optimal when comparing adults of different sexes, RPL13 and EF1α were optimal when analyzing different tissues, and TATA and ACTIN were optimal for different diapause states. These results provide a valuable foundation for future RT-qPCR analyses of A. japonicus gene expression and function under a range of experimental conditions.